The video promotion is more effective to promote about Malacca/ Syamsul Firdaus Haji Sardi - Sardi, Syamsul Firdaus (2015)
Tourism has been regarded as all industry which can contribute to tile economic prosperity of a country as much as to the quality of life, international understanding, national culture and heritage. This belief has encouraged governments toinvest heavily on the tourism industry. This study is examines the tourism phenomena with reference to the historic city of Malacca. Its main aim is to review the state of tourism industry in the area of Malacca, identify strengths and weaknesses, and make recommendations of consideration so as to promote Melaka as one of the most popular tourist destinations within the region.